Proyecto de factibilidad para la creación de una empresa importadora y comercializadora de equipos y dispositivos cuánticos para tratamientos médicos en la ciudad de Quito - Meléndez Ortega, Paola Gabriela (2014)
The present research is performed in order to identify the key aspects for creating an import and marketing of quantum computers in the city of Quito, considering that this work is a legal requirement of the University to achieve the title third level. The selected topic is the result of field research, and that by observing the importance of using quantum computers in medicine today is determined. As shown in development work, these teams have achieved wide acceptance in the healthcare market, are based on Russian technology and in nonlinear bio-resonance, being the latest proposal in the field of diagnosis that allows to know reliably and accurately the prognosis of the disease and even seeks anticipate the onset of symptoms, these devices allow the physician to determine more precisely the type of evidence that requires the patient to complete the diagnosis and ensure the successful outcome of treatment